The decisive factors and the types of corporate social responsibility activities implemented by public listed companies in Malaysia / Mohd Farhan Mohd Areffin - Mohd Areffin, Mohd Farhan (Faculty of Business and Management, 2009)
This study will focus on “The Decisive Factors and the Types of Corporate Social Responsibility Activities implemented by Public Listed Companies in Malaysia”. The terms ‘Corporate Social Responsibility’ can be defined as organizations contribute which is freely giving something to specific person or group. The purpose of this study is to identify areas of corporate social responsibility activities that are commonly and rarely adopted by Public Listed companies in Malaysia so that improvement can be made in order to sustain the development of social, economy and environment. The corporate organization should know the benefits of implementing the corporate social responsibility activities which is profitable for the firm and also contributes to the social, economy and environment well-being of the country. Through this research, the researcher fined out that the most favorite type of corporate social responsibility activities adopted by Public Listed companies in Malaysia is abundantly focusing on the social development programs. Furthermore, the result from this research shows that the leading companies that are actively involved in corporate social responsibility activities are the local firms rather than Multinational Corporations. Meanwhile, the leading industry involve in corporate social responsibility activities are tertiary industry companies which offer services, ICT, property & investment, telecommunication and other type of service companies. Moreover, the researcher also found companies that already operate their business activity between 21 up to 40 years are more actively participating and implementing corporate social responsibility activities